Covid-19 Crisis, Economic Hardships and Schooling Outcomes - Esther Gehrke; Friederike Lenel; Claudia Schupp (Center for Economic Studies and ifo Institute (CESifo), 2022)
We combine phone-survey data from 2,200 students collected in July-August of 2020 with student-level administrative data from 54 schools in four Northwestern provinces of Cambodia to investigate the implications of the COVID-19 pandemic for grade 9 students. These students were particularly vulnerable to dropping out of school prematurely due to the crisis. We find that most students kept studying during the crisis, returned to school to participate in the lower-secondary graduation exam after schools reopened, and transitioned to high school thereafter. However, we also find that students' exposure to the economic downturn had substantial implications: The likelihood that the father experienced income losses due to the crisis is negatively associated with a student's propensity to study during school closure, participation and performance in the final exam, and with the likelihood to transition to high school. In contrast, the likelihood that the mother experienced income losses is positively associated with student studying during the crisis, with participation in the final exam and with transition to high school — potentially because mothers used the time at home to encourage their children to study.
Keywords: I18; I25; O12; 330; Covid-19; schooling; Cambodia